International Organizations in Global Social Governance - Martens, Kerstin; Niemann, Dennis; Kaasch, Alexandra (Global Dynamics of Social Policy, 2021)
This open access book enhances and systematizes our understanding of IOs in global social governance. It provides studies on a variety of social policy fields in which different, but also the same, International Organizations (IOs) operate. The chapters shed light on IO involvement in a particular social policy field by describing the population of participating IOs; exploring how a particular global social policy field is constituted as a whole, and which dominant IOs set the trends. The contributors also examine the discourse within, and between, these IOs on the respective social policies. As such, this first-of-its kind book contributes to research on social policy and international relations, both in terms of theoretical substantiation and empirical scope.